On the domains of analyticity of complex power series with independent random coefficients - Meredov , B. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We consider a complex power series with independent random coefficients and investigate the possibility of analytic extension of its sum beyond the boundaries of the domain of convergence.